The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/hjr.0b013e328337ccbd
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carotid lesions add to cardiovascular risk prediction

Abstract: In our experience, the incidence of CV events is enhanced in patients with subclinical-ATS. Increased IMT and ACP predict CV events and improve the risk stratification of asymptomatic patients aged greater than 45 years and with a cluster of RFs, in a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…Carotid Doppler is a simple and cheap method to assess state of the vessels and detect early vascular damage . Although the HCV chronically infected patients are usually characterised by a favourable lipoprotein profile, low platelet count and low blood pressure, several studies suggested a high prevalence of carotid atherosclerosis due to the pro‐inflammatory and metabolic alteration, insulin resistance/diabetes proper of these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Carotid Doppler is a simple and cheap method to assess state of the vessels and detect early vascular damage . Although the HCV chronically infected patients are usually characterised by a favourable lipoprotein profile, low platelet count and low blood pressure, several studies suggested a high prevalence of carotid atherosclerosis due to the pro‐inflammatory and metabolic alteration, insulin resistance/diabetes proper of these patients .…”
Section: Discussionmentioning
confidence: 99%
“…It is suitable for large population study, because this measurement is non-invasive, low-cost and convenient. Moreover, CIMT has been used in clinical trials to evaluate the efficacy of anti-diabetic, anti-hyperlipidemia and anti-hypertensive treatments [5-8]. …”
Section: Introductionmentioning
confidence: 99%
“…A thicker IMT predicts coronary heart disease [28], stroke [29], and myocardial infarction [29,31]. A 5,5 years-follow-up showed that the risk of myocardial necrosis increases for about 10- 15% just if IMT increases for 0,1 mm while the risk of stroke increases for about 13- 18% [37]. Moreover other studies underlined that the Metabolic Syndrome could produce a more rapid deterioration of brain function, because it seems to be related to a low gray matter cerebral blood flow (GM-CBF) and to a lower immediate memory function if compared to control subjects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, preclinical atherosclerosis added to traditional risk factors can improve the cardiovascular risk prediction [37,47], especially in presence of metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%